Greenland, view of Kjerulf Fjord through to Dicksons Fjord and Hisinger Gletscher - Boyd, Louise Arner, 1887-1972 (1931)
August 2, 1931. Kjerulfs [Kjerulf] Fjord. Through to Dickson [Dicksons] Fjord. In background: rising above the glacier can be seen a peak or high nanatak. It may be an outstanding peak of another range apart from Scoop Mt. [Mountain] range. On right in background is range of mountains forming the west side of Left Valley, running S.E. to here -- where mts. [mountains] turn and go to the S.S.W. and form the eastern side of Hisinger Glacier [Hisinger Gletscher] in Unknown Valley. In foreground; pond-like lake (sourced by waters off Hisinger Glacier [Hisinger Gletscher], in background) and the stream of Left Valley shown flowing out of this lake. Photo taken on eastern side of Left Valley at inner end (S.E.) looking S.S.W.